2012
DOI: 10.1093/rheumatology/kes315
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis without antinuclear antibodies or Raynaud's phenomenon: a multicentre study in the prospective EULAR Scleroderma Trials and Research (EUSTAR) database

Abstract: We have identified a very small subgroup of SSc patients who lack both circulating ANA and RP, none of whom fulfils the diagnostic criteria for any known SSc mimic. Prospective studies are needed to elucidate the clinical presentation, evolution and outcome of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
1
17
0
2
Order By: Relevance
“…Patients within this group generally do not have organ involvement, Raynaud's phenomenon and also have negative antibodies; these data may suggest that even though they are classified as SSc probably they do not have an overt disease, and that non-specific capillary abnormalities may precede a full-blown scleroderma pattern. This subgroup has been recently studied in depth by other EUSTAR members (Schneeberger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Patients within this group generally do not have organ involvement, Raynaud's phenomenon and also have negative antibodies; these data may suggest that even though they are classified as SSc probably they do not have an overt disease, and that non-specific capillary abnormalities may precede a full-blown scleroderma pattern. This subgroup has been recently studied in depth by other EUSTAR members (Schneeberger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this Chinese cohort of SSc subjects, 4.2% of subjects were negative for ANA, which is approximately in agreement with published ndings. EUSTAR has also identi ed their subjects without ANA or Raynaud's phenomenon as a very small subgroup of SSc [8]. Hamaguchi and colleagues [9] reported that the absence of ANA was found in 5% SSc subjects in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although—or because of—independence from industry, the database facilitated novel treatment approaches, which assist to alter the course of the disease significantly 15 16. This will apply also to the rare juvenile32 the late-onset33 and the ANA/Raynauds’ negative34 forms. Fifth, perhaps the most important and durable in the outcome of the EUSTAR initiative, is the launching of an immense scientific interest in the disease, which resulted in an increasing number of spinoff cooperative international projects,35 for example, together with the US-based scleroderma trials consortium (SCTC) that far exceeds the initial idea of a ‘database’.…”
Section: How Has the Eustar Database Contributed To New Understandingmentioning
confidence: 99%